PENGARUH LINGKUNGAN KERJA, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN KANTOR AKUNTAN PUBLIK (KAP) JANSEN DAN REKAN - Nurani Teguh Dhermawan; Ismail Razak (Jurnal Ekonomi dan Industri, 2023)
The purpose of this study was to analyze the effect of work environment, organizational culture, and work motivation on job satisfaction of the employees of the Jansen and Partners Public Accounting Firm. The data collection method is by distributing questionnaires to employees of the Jansen and Partners Public Accounting Firm. The sampling technique used is saturated sampling. Data were analyzed using simple linear regression analysis and multiple linear regression analysis. The result of this study indicated that the work environment, organizational culture, and work motivation has a positive and significant effect on job satisfaction of the employees of the Jansen and Partners Public Accounting Firm either partially or together.